Cowpea in traditional cropping systems - Mortimore, M.; Singh, B.; Harris, F.; Blade, S. (1997)
The production of cowpea in Africa and America is reviewed briefly. In traditional cropping systems in West Africa, a diversity of both systems and varieties is observed. The contribution of cowpea to overall productivity is small (on average about a tenth of grain yields, averaging 1.5 l/ha), and this fact, together with drought and pest vulnerability, creates a paradox in view of its widespread popularity. The answer to this paradox may lie in cowpea's labor complementarity with the major grain crops, and its value for human diets, livestock fodder, and soil nutrient interactions. Farming systems in this region are changing and are being driven by four sets of factors: population growth (increasing land scarcities), market integration (urban demand), technological change (new cultivars and production methods), and intensification (adaptive change in soil fertilization regimes). Cowpea plays an important role in nutrient cycling (N) in the high-intensity system of the Kano close settled zone in northern Nigeria, while genetic diversity is exploited to minimize risk in the drier areas. Research and extension agencies should recognize the systemic linkages of cowpea in maintaining sustainable farming systems, and the need to support diversity and indigenous technology.